2020
DOI: 10.1002/sctm.20-0381
|View full text |Cite
|
Sign up to set email alerts
|

Phase I clinical trial of intra-bone marrow cotransplantation of mesenchymal stem cells in cord blood transplantation

Abstract: Mesenchymal stem cells (MSCs) have immunomodulatory properties and support hematopoiesis in the bone marrow (BM). To develop a new strategy to not only prevent graft-vs-host disease (GVHD) but also to enhance engraftment, a phase I trial of cord blood transplantation (CBT) combined with intra-BM injection of MSCs (MSC-CBT) was designed. Third-party BM-derived MSCs were injected intra-BM on the day of CBT. The conditioning regimen varied according to patient characteristics. GVHD prophylaxis was tacrolimus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Moreover, the lack of HLA-ABC marker in the non-target organs of blood, bone marrow, liver, lungs, and spleen confirmed safety of intraosseous DEC administration by the lack of evidence of DEC cell migration and lodging in the lungs. This supports the benefits of the intraosseous when compared to intravenous administration of cell-based therapies (Goto et al 2018(Goto et al , 2021Lee et al 2013;Marktel et al 2019;Siemionow et al 2005) where the "first-pass" accumulation of cells in the lungs was reported for MSC delivered via intravenous route (Krueger et al 2018).…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, the lack of HLA-ABC marker in the non-target organs of blood, bone marrow, liver, lungs, and spleen confirmed safety of intraosseous DEC administration by the lack of evidence of DEC cell migration and lodging in the lungs. This supports the benefits of the intraosseous when compared to intravenous administration of cell-based therapies (Goto et al 2018(Goto et al , 2021Lee et al 2013;Marktel et al 2019;Siemionow et al 2005) where the "first-pass" accumulation of cells in the lungs was reported for MSC delivered via intravenous route (Krueger et al 2018).…”
Section: Discussionsupporting
confidence: 77%
“…Similar findings of higher engraftment rate and amelioration of multi-organ function were confirmed by other investigators following intraosseous administration of bone marrow, cord-blood cells and MSC tested in clinical trials and treatment of blood disorders in both, the adult and pediatric patients’ population [ 72 76 ]. Recent Phase I clinical trial confirmed better efficacy of engraftment and safety after intra-bone co-administration of cord blood cells and MSC [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, researchers have paid more attention to alternative routes of stem cell administration to reduce the ineffective homing of donor cells[ 55 , 56 ]. Animal model studies have highlighted that compared with intravenous infusion, intra-bone marrow injections for HSPC transplantation are more effective in promoting hematopoietic reconstitution and reducing the incidence of GVHD[ 57 - 59 ]. At present, the clinical application of intra-bone marrow injections is still in its infancy and is mostly used for umbilical cord blood cell transplantation.…”
Section: Hematopoietic Reconstitution After Bone Marrow Transplantationmentioning
confidence: 99%